The classification of slurries and other suspensions using ultrasonic techniques - Davies, Andrew Lewis (Department of Electrical Engineering, 2016)
The attenuation of ultrasonic waves travelling through a liquid containing a suspension of solids is highly dependent on frequency. At low frequencies, where the wavelength is long compared to the particle size, the particles move with the wave with some phase lag which gives rise to a loss component. At high frequencies, where the wavelength can be made comparable to, and ultimately less than the particle diameter, there is still some movement but most of the energy is lost to the wave by scattering. In this work, is attenuation used to characterize the suspension, and is treated in terms of these two components. Absorption which is the conversion of energy into heat and scattering from the actual particles. The former is expressed as loss (dB) per wavelength and increases with frequency, while the latter, in the short wavelength scattering zone simply obstructs the wave.